OPTIMALISASI WORKING CAPITAL PADA PERUSAHAAN FINANCIAL CONSTRAINTS DI INDONESIA - Rika Rahayu; Maratus Zahro; Dewi Maryam (Universitas Medan Area, 2020)
This research aimed to examine the effect of company size, leverage, cashflow, profitability ratio, and tangible asset on the cash conversion cycle at manufacturing companies in Indonesia. While, the research wan the quantitative. Moreover, the research sample consisted of 30 manufacturing companies from 2016 to 2018. The sampling collection technique used purposive sampling, in which the sample was taken based on criteria given. In addition, the data analysis technique used multiple linear regression. This research used company size, leverage, cashflow, profitability ratio, and tangible asset as independent variable and cash conversion cycle as dependent variable. For the research result, it concluded as follows, company size which is proxied by logarithm of total assets had negative effect on the cash conversion cycle; leverage had positive effect on the cash conversion cycle; cashflow which is proxied by net profit/loss ratio had positive effect on the cash conversion cycle; profitabiity ratio which is proxied by return on asset did not effect on the cash conversion cycle; tangible asset had negative effect on the cash conversion cycle..